The Use Of Lexical Repetition And Patterning In Written Compositions Of Jordanian Students Majoring In English Language And Literature At Mu’tah University: A Case Study - Khotaba, Eissa Hamid Al (2010)

(untitled)
In an EFL (English as a Foreign Language) context, writing is a skill that EFL learners must acquire as that would certainly help them in their future career (Mirhosseini, 2009). Many researchers such as Hoey (1991), Wong (2004), Klebanov and Shamir (2006), Morris (2007) and Kai (2008) found out that EFL (English as a Foreign Language) and ESL (English as a Second Language) learners’ written essays are difficult to understand as they lack coherent structure and organisation. These researchers, in particular Hoey (1991), argue that lexical repetition and patterning in written texts are necessary to produce coherent and well-organised written essays.